2021
DOI: 10.1002/jsfa.11167
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of the effect of drought on growth and yield of pomegranates by foliar spraying of different sizes of selenium nanoparticles

Abstract: BACKGROUND Drought is a very important environmental stressor, which has negative effects on the growth of trees, decreasing their yield. The role of different‐sized selenium nanoparticles (Se‐NPs) in the mitigation of environmental stresses such as drought in crops has not yet been investigated. RESULTS Trees treated with Se‐NPs displayed higher levels of photosynthetic pigments, a better nutrient status, better physical parameters (especially fruit cracking) and chemical parameters, a higher phenolic content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 34 publications
(50 reference statements)
0
25
0
Order By: Relevance
“…The decrease in carboxylation, gaseous exchange, and rate of photosynthesis while the increase in lipid peroxidation, electrolyte leakage was also reported in six ecotypes of T. aestivum under water stress (Khalvandi et al 2021). They also considerably decrease the growth of Oryza sativa (Ahmed et al 2021a), Medicago sativa (Tyshchenko et al, 2020), Beta vulgaris (AlKahtani et al 2021, Nicotiana tabacum (Begum et al 2021), Punica granatum (Zahedi et al 2021) and affect various other crops. This situation reinforces the need to develop a suitable approach that decrease the damaging effects of water stress and improves the germination, establishment, and yield of crops.…”
Section: Introductionmentioning
confidence: 84%
“…The decrease in carboxylation, gaseous exchange, and rate of photosynthesis while the increase in lipid peroxidation, electrolyte leakage was also reported in six ecotypes of T. aestivum under water stress (Khalvandi et al 2021). They also considerably decrease the growth of Oryza sativa (Ahmed et al 2021a), Medicago sativa (Tyshchenko et al, 2020), Beta vulgaris (AlKahtani et al 2021, Nicotiana tabacum (Begum et al 2021), Punica granatum (Zahedi et al 2021) and affect various other crops. This situation reinforces the need to develop a suitable approach that decrease the damaging effects of water stress and improves the germination, establishment, and yield of crops.…”
Section: Introductionmentioning
confidence: 84%
“…The employment of NPs has revolutionized the agricultural field as a compelling strategy to enhance plant growth and development under normal as well as stressful situations (Gogos et al, 2012;Raliya et al, 2017;Lowry et al, 2019). Recent studies have confirmed the elevation of plant strength against drought stress upon treatment with NPs (Jaberzadeh et al, 2013;Aghdam et al, 2016;Zahedi et al, 2021).…”
Section: Drought and Plant Life: From Evolution To Nanorevolutionmentioning
confidence: 99%
“…The NP‐induced reduction in stress‐induced ROS levels plays a key role in reducing the negative impacts of stresses, including drought, on plant growth (Djanaguiraman et al, 2018; Jalil & Ansari, 2019; Sharma et al, 2019; Ali et al, 2021). For instance, pomegranate trees under drought stress whose leaves were treated with 20 mg/L of selenium NPs (Se‐NPs; 10 and 50 nm) showed an elevated phenolic and photosynthetic pigment content, increased osmolyte concentration and improved nutrient status in comparison to untreated trees (Zahedi et al, 2021). Along with these changes, Se‐NPs also reduced drought‐induced accumulation of H 2 O 2 and lipid peroxidation via enhanced antioxidant activity.…”
Section: Np‐mediated Physiological and Biochemical Mechanisms Of Drou...mentioning
confidence: 99%
See 1 more Smart Citation
“…Drought stress is one of the main environmental factors limiting plant growth and productivity [1,2]. However, plants have developed a series of physiological and anatomical modifications in response to drought stress [3].…”
Section: Introductionmentioning
confidence: 99%